Breaking the Chain of Violence: A Study of Policy Implementation on Child Protection in Samarinda City, Indonesia - Rande, Santi; Asmarani, Mayada (Manunggal Halim Jaya, 2025)
This study aims to analyze the implementation of child protection policies for victims of violence by the Office of Women Empowerment and Child Protection (DP2PA) in Samarinda City using Edward III's implementation model as the analytical framework. The model emphasizes four key indicators: communication, resources, disposition, and bureaucratic structure. This qualitative research employs a descriptive method through in-depth interviews, observation, and documentation with key informants from government agencies, social institutions, and the general public. The findings show that the policy implementation has been carried out relatively well, especially regarding communication and disposition. DP2PA and UPTD PPA actively engage in public outreach and inter-agency coordination and demonstrate a strong commitment to handling child abuse cases. However, limited human resources and budget constraints remain significant challenges, mitigated through regular training and efficient budget management. The bureaucratic structure is considered adequate, as evidenced by precise task distribution and integrated standard operating procedures (SOPs). These findings suggest that the success of policy implementation is influenced not only by the existence of regulations but also by the synergy among stakeholders, the commitment of implementers, and effective communication strategies. Theoretically, this study reinforces the applicability of Edward III's model in the context of social policy. At the same time, practically, it offers valuable insights for local governments to strengthen holistic child protection systems.